L’utilisation de la phytothérapie pour le traitement des infections respiratoires dans des régions de Sétif, Algérie - KRAOUCHI , Narimane; AGGOUN , Samah; LAIB , Ouissal; HAJIRA , Sabrina Encadrent (Université Sétif 1 Ferhat Abbas . Faculté des Sciences de la Nature et de la Vie, 2025)
With the resurgence of respiratory infections and the diversity of their causes, the use of traditional medicine—particularly herbal remedies—has become a widespread practice, especially in areas where access to modern healthcare remains limited. In this context, a field survey was conducted in the wilaya of Sétif, involving 193 participants, including residents from various municipalities as well as herbalists, with the aim of documenting and analyzing the use of medicinal plants in treating respiratory illnesses. The study revealed that 98.4% of respondents had already used medicinal plants to treat symptoms such as colds, coughs, and bronchitis. The most represented age group was young adults (20–30 years), accounting for 63.2% of the sample, while women made up 83.4%, highlighting their central role in preserving and transmitting traditional therapeutic knowledge.
مع تزايد وتيرة الإصابات بالأمراض التنفسية وتنوع مسبباتها، أصبح اللجوء إلى الطب التقليدي، وخاصة التداوي بالأعشاب، ممارسة شائعة على نطاق واسع، خصوصًا في المناطق التي لا يزال فيها الوصول إلى الرعاية الصحية الحديثة محدودًا. وفي هذا السياق، أُجريت دراسة ميدانية في ولاية سطيف شملت 193 مشاركًا، من بينهم سكان من عدة بل ديات وعشّابون، بهدف توثيق وتحليل استخدام النباتات الطبية في علاج الأمراض التنفسية. كشفت نتائج الدراسة أن ٪ 98.4 من المشاركين سبق لهم استخدام النباتات الطبية لعلاج أعراض مثل الزكام والسعال والتهاب القصبات. وكانت الفئة العمرية الأكثر تمثيلًا هي فئة الشباب بين 20 و 30 سنة بنسبة 63.2 ٪، بينما شكّلت النساء 83.4 ٪ من العينة، مما يبرز دورهن المحوري في نقل واستخدام المعارف العلاجية التقليدية.